Desain UI/UX e-Marketplace UMKM Pastry & Bakery (Bakehouse) dengan Metode Lean UX - Radinka Frisia Mulia; Agussalim Agussalim; Rizka Hadiwiyanti (Sekawan Institut, 2025)
Micro, small, and medium enterprises (MSMEs) currently play a crucial role in the Indonesian economy. However, there are several challenges faced by MSME managers in Indonesia such as marketing and digitalization problems. In overcoming these challenges, MSMEs need help in managing business processes more effectively and efficiently, by using e-marketplaces. This e-marketplace application was designed using the Lean UX approach, which involves four key stages: declare assumption, create an Minimum Viable Product (MVP), run an experiment, feedback and research. The Lean UX method supports efficient digital platform development, focuses on customer needs, accelerates trend adaptation, and enhances customer experience and loyalty through feedback-driven iterations. The primary objective of this process is to facilitate the management of information about registered MSMEs in the pastry and bakery sector. Based on this study, the results showed that the design of the BakeHouse e-marketplace interface with the Lean UX approach was able to meet the declare assumption needs of users. After going through two iterations with design improvements, the evaluation results indicated a significant improvement compared to the first iteration. This is evidenced by the increase in score from 70 to 93 for the evaluation from MSMEs owners and a score of 67.5 to 89.5 for the evaluation from customers on the System Usability Scale assessment.